2002
DOI: 10.1074/jbc.m209085200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Cholesterol Transporter ABCA1 in Central Nervous System Cells by Liver X Receptor Agonists Increases Secreted Aβ Levels

Abstract: The expression, function, and regulation of the cholesterol efflux molecule, ABCA1, has been extensively examined in peripheral tissues but only poorly studied in the brain. Brain cholesterol metabolism is of interest because several lines of evidence suggest that elevated cholesterol increases the risk of Alzheimer's disease. We found a largely neuronal expression of ABCA1 in normal rat brain by in situ hybridization. ABCA1 message was dramatically up-regulated in neurons and glia in areas of damage by hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
133
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(144 citation statements)
references
References 60 publications
8
133
2
1
Order By: Relevance
“…That ABCA1 can directly influence Ab has been demonstrated (Fukumoto et al 2002), and more recent evidence suggests that ABCA1 also interacts with APOE in the CNS (Hirsch-Reinshagen et al 2004). In the present study, we suggest that genetic variants of ABCA1 may influence CSF Ab 1-42 levels, possibly reflecting its involvement with Ab metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That ABCA1 can directly influence Ab has been demonstrated (Fukumoto et al 2002), and more recent evidence suggests that ABCA1 also interacts with APOE in the CNS (Hirsch-Reinshagen et al 2004). In the present study, we suggest that genetic variants of ABCA1 may influence CSF Ab 1-42 levels, possibly reflecting its involvement with Ab metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that deficiency of ABCA1 in the brain leads to a specific decrease in APOE levels (Hirsch-Reinshagen et al 2004;Wahrle et al 2004). Interestingly, ABCA1 shares a commonality with APOE in that it appears to be involved in Ab metabolism (Fukumoto et al 2002); this is supported by evidence suggesting a relationship between cholesterol metabolism and Ab metabolism (Simons et al 1998(Simons et al , 2001Kojro et al 2001). Emerging data thus suggest that ABCA1 plays an important role in lipid metabolism in both peripheral tissues and the central nervous system (CNS) and, like APOE, may also influence Ab.…”
Section: Introductionmentioning
confidence: 99%
“…With its expression in liver and brain, ABCB1 -the prototype of the B subclass of transporters -and ABCA1 regulate the high-density lipoprotein levels in the plasma and cholesterol contents of several cell types in these organs [106][107][108][109][110][111][112][113][114]. Most interestingly, the ABCB1 transporter also shows strong expression in neurons of the hippocampus formation, particularly in the granule cells of the DG [85].…”
Section: Abc Transporters In the Brainmentioning
confidence: 99%
“…The discovery that SNPs in genes involved in cholesterol metabolism such as Abca1, Abca2, and Cyp46 are associated with increased risk for AD further strengthens this notion (25)(26)(27). Several groups have examined effects of LXR on APP processing (14,28,29), which is sensitive to cellular sterol levels (23). These studies support a possible role for ATP-binding cassette A1 (ABCA1), a transporter for cholesterol and phospholipids and a direct transcriptional target of LXR, in AD.…”
mentioning
confidence: 99%